The Role of Empathy in Social Intelligence to Reduce Cyberbullying Among Adolescents - Solang, Deetje Josephine (GoAcademica Research & Publishing, 2025)
The increasingly widespread phenomenon of online bullying among adolescents raises concerns about the social and emotional development of the younger generation. Although various interventions have been implemented, efforts to reduce this negative behavior often fail to address the root cause, which is related to adolescents' psychosocial aspects. One important dimension of social intelligence believed to play a significant role in reducing digital bullying is empathy, especially in the context of online interactions. This study used a qualitative approach, collecting data from various literature sources, previous study findings, and in-depth analysis of narratives relevant to the research focus. This study aims to explore how the empathy dimension of social intelligence can contribute to reducing cyberbullying among adolescents. The results show that strengthening empathy can be an important foundation in shaping adolescents' social awareness in the digital space. Empathy has been shown to reduce the urge to engage in verbal and non-verbal aggression online and increase an individual's willingness to act as a mediator or advocate for victims. Fostering empathy through character education, meaningful social interactions, and empathetic communication training is a strategic step in creating a healthier and safer digital space for adolescents.